Ellipsis in comparatives - Lechner, Winfried, 1967- (Studies in generative grammar ;, 2004)
Generative analyses of comparatives traditionally include two construction specific ellipsis operations, Comparative Deletion and Comparative Ellipsis. Drawing from a wide array of new data, the present monograph develops a novel, directly semantically in.